Development of a Smart Lighting Android-based Application using Bluetooth Low Energy - Batista, Daniel Filipe Vicente (2016)
The emergence of the Internet of Things (IoT) allowed new developments on home and building automation with devices that provide more power efficiency and adaptation to our needs. Therefore, this thesis presents a study about Blue- tooth Low-Energy and its application on a IoT context, through smart devices designed for home applications and to be integrated in smart home system. It is also investigated the advantages and disadvantages of Bluetooth Low Energy (BLE) over other communication protocols for IoT end-devices. State-of-art Smart Lighting Android-based Application using Bluetooth Low Energy (SLABLE) is implemented with BLE and covers three application layers: first a interactive mobile application for Android OS. Then the middleware to manage communication and the data gathered, implemented in a BLE built-in System-on-Chip (SoC) with the respective programming for tasks as sending and receiving informations or commands and an illumination automatic control, de- veloped in Arduino IDE. Lastly, an hardware layer that consists in sensors and a lamp dimming driver, to be integrated on a circuit board small enough to fit in already installed equipment boxes. The implemented system purpose is a transversal integration between all layers . Moreover, based on energy consumption study, it is shown that BLE modules are proven to be a good solution for IoT development due to their low-power consumption, also, for data exchange reliability and processing capacity to control and perform several actions at the same time.